Investigation of commonly used assessment methods for predicting fall risk in the elderly - Dengiz, Aziz; Aytepe, Ahmet; Sirri, Bayram; Efe, Mehmet (Pergamon-Elsevier Science Ltd, 2025)
Aim: This study aimed to evaluate the effectiveness of four different commonly used assessment methods Berg Balance Scale (BBS), Timed Up and Go Test (TUG), Modified Falls Efficacy Scale (MFES), and Morse Fall Scale (MFS) in predicting fall risk in elderly. Method: The study included 195 participants (97 female, mean age: 69.82 +/- 7.45 years) aged 60 and above. The BBS, TUG, MFES, and MFS were used to asses fall risk. Logistic regression analysis was conduct. Results: The addition of independent variables significantly reduced the -2 Log Likelihood value (from 222.015 to 49.196), and the Nagelkerke R2 value was 0.865. The Hosmer-Lemeshow goodness-of-fit test (p = .738) and ROC analysis (AUC 0.958-0.972) confirmed the model's strong fit and high discriminative power. The MFS (B = 0.120, p = .001, Exp(B) = 1.128) and the TUG(B = 0.542, p = .004, Exp(B) = 1.720) were significantly associated with fall risk. In contrast, the MFES and BBS did not show statistically significant effects. Conclusions: The MFS and TUG are particularly effective in identifying fall risk in elderly individuals. However, using these tests alone may have limited predictive power, highlighting the importance of a multidisciplinary approach for fall risk assessment.
Keywords: Elderly; Fall risk; Timed up and go test; Morse fall scale